Analisis Pengembangan Usaha Feyre Makeup Art pada Media Sosial Instagram untuk Meningkatkan Brand Awareness - Gunawan Gunawan; Faridah Nurfauziah Furqon (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
This Feyre Makeup Art is a makeup service business aiming to enhance brand awareness through social media, especially Instagram. This study analyzes the business development strategy of Feyre Makeup Art in increasing brand awareness and strengthening its position in the Bandung beauty market. The research focuses on digital marketing strategies, including the role of visual content, implementation of effective personal branding, and evaluation using TAM, SAM, and SOM analysis.Findings indicate that the optimization of personal branding, consistency in visual content, and audience engagement significantly boost brand awareness. However, several Instagram features such as Reels, live broadcasts, and paid advertisements have yet to be fully utilized to expand reach and visibility.This research highlights the importance of an integrated social media strategy, including collaboration with local influencers and maximizing the use of Instagram's advanced features, in enhancing audience interaction and sustaining Feyre Makeup Art’s position as one of Bandung’s leading makeup artists.The study recommends that Feyre adopt a holistic digital approach to improve engagement, expand market coverage, and support long-term growth in the competitive beauty industry.